2011
DOI: 10.4238/vol10-2gmr1016
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin and transferrin saturation levels in β0 and β+ thalassemia patients

Abstract: ABSTRACT.There have been few studies on the mutations that cause heterozygous beta-thalassemia and how they affect the iron profile. One hundred and thirty-eight individuals were analyzed, 90 thalasemic β 0 and 48 thalasemic β + , identified by classical and molecular methods. Mutations in the hemochromatosis (HFE) gene, detected using PCR-RFLP, were found in 30.4% of these beta-thalassemic patients; heterozygosity for H63D (20.3%) was the most frequent. Ferritin levels and transferrin saturation were similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
2
0
4
Order By: Relevance
“…The role of H63D mutation polymorphism in β-thal major or carrier conditions has been studied in regions with a high incidence of H63D, such as in Southern Europe and Asia. Various studies have yielded conflicting conclusions (shown in Table 1): some studies from Italy, Portugal, India and Egypt suggested that iron overload might arise from the interacting effect of β-thal with homozygous or even heterozygous H 63 D mutations (13,(19)(20)(21)(22)(23); other reports from Italy, India, Thailand, Brazil and Spain indicated that the iron status was not related to the H63D mutation status (24)(25)(26)(27)(28)(29). The discrepancy may be due to the sample size, hereditary background variations in different racial populations, the sex ratio and the severity of thalassemia.…”
Section: Discussionmentioning
confidence: 98%
“…The role of H63D mutation polymorphism in β-thal major or carrier conditions has been studied in regions with a high incidence of H63D, such as in Southern Europe and Asia. Various studies have yielded conflicting conclusions (shown in Table 1): some studies from Italy, Portugal, India and Egypt suggested that iron overload might arise from the interacting effect of β-thal with homozygous or even heterozygous H 63 D mutations (13,(19)(20)(21)(22)(23); other reports from Italy, India, Thailand, Brazil and Spain indicated that the iron status was not related to the H63D mutation status (24)(25)(26)(27)(28)(29). The discrepancy may be due to the sample size, hereditary background variations in different racial populations, the sex ratio and the severity of thalassemia.…”
Section: Discussionmentioning
confidence: 98%
“…Sugere-se que o traço β-talassêmico se associe com razão hepcidina/ferritina reduzida (SULOVSKA et al, 2016;JONES et al, 2015;GUIMARÃES et al, 2015) e valores de absorção de ferro maiores que os esperados para a magnitude das suas reservas corporais (ZIMMERMAN et al, 2008). Além disso, observações clínicas de uma grande heterogeneidade do status de ferro, mesmo entre carreadores de uma mesma mutação HBB, motivou a investigação de possíveis efeitos sinérgicos entre a β-talassemia menor e genótipos associados com a hemocromatose hereditária (WILSON et al, 2015;ESTEVÃO et al, 2011;MADANI et al, 2011;YAMSRI et al, 2007;GARWAL et al, 2005;MARTINS et al, 2004;MELIS et al, 2002).…”
Section: Discussionunclassified
“…Em particular, é postulado que a heterozigose das mutações HBB possa ter conferido vantagens seletivas para mulheres, crianças e adolescentes expostos a dietas com baixo conteúdo do mineral (ESTEVÃO et al, 2010;HOORFAR et al, 2008MEHTA & PANDYA, 1987. No entanto, não há consenso quanto às diferenças na incidência de deficiência ou sobrecarga de ferro entre indivíduos sem hemoglobinopatias e casos com βtalassemia menor (MARUF-UR-RAHMAN et al, 2011;ESTEVÃO et al, 2011;HOORFAR et al, 2008;PIPERNO et al, 2000;NOBILI et al, 2000;QURESHI et al, 1995;HINCHLIFFE & LILLEYMAN, 1995;GALANELLO et al, 1990;MEHTA & PADNYA, 187;WHITE et al, 1986). (PIPERNO et al, 2000).…”
Section: Discussionunclassified
See 2 more Smart Citations